2013
DOI: 10.1007/s00122-013-2146-1
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the density of markers around a major QTL controlling resistance to angular leaf spot in common bean

Abstract: Angular leaf spot (ALS) causes major yield losses in the common bean (Phaseolus vulgaris L.), an important protein source in the human diet. This study describes the saturation around a major quantitative trait locus (QTL) region, ALS10.1, controlling resistance to ALS located on linkage group Pv10 and explores the genomic context of this region using available data from the P. vulgaris genome sequence. DArT-derived markers (STS-DArT) selected by bulk segregant analysis and SCAR and SSR markers were used to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 74 publications
1
45
0
1
Order By: Relevance
“…Variety G5686, also a documented source of resistance (Mahuku et al, 2009) on Pv10, identified in both G5686 (Keller et al, 2015) and CAL143 (Oblessuc et al (2012(Oblessuc et al ( , 2013 were officially named as Phg-4 and Phg-5 (Souza et al, 2015;).…”
Section: Discussionmentioning
confidence: 99%
“…Variety G5686, also a documented source of resistance (Mahuku et al, 2009) on Pv10, identified in both G5686 (Keller et al, 2015) and CAL143 (Oblessuc et al (2012(Oblessuc et al ( , 2013 were officially named as Phg-4 and Phg-5 (Souza et al, 2015;).…”
Section: Discussionmentioning
confidence: 99%
“…The PhaseolusGenes marker database has become an essential tool for cataloging bean marker diversity so that the breeding community can utilize marker information from multiple sources to facilitate MAS (Gonçalves-Vidigal et al, 2011Reinprecht et al, 2013;Oblessuc et al, 2013Oblessuc et al, , 2015Aranda et al, 2014;Keller et al, 2015;Sousa et al, 2015;Coimbra-Gonçalves et al, 2016;Perseguini et al, 2016). Because genomic resequencing of breeding parents is today a more routine practice with the lowered cost of sequencing, the PhaseolusGenes database should evolve from a marker database into a sequence database, which includes not only the current markers but also the increasingly large number (> 2,000) of genotypes that have been sequenced, including the 16 parental genotypes of the ABC projects (T. Miller and P. Gepts, unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative trait locus (QTL) mapping had also been used to identify multiple resistance loci in Andean germplasm. Seven QTLs on five chromosomes were identified in a IAC-UNA × CAL 143 recombinant inbred population and named ALS2.1, ALS3.1, ALS4.1, ALS4.2, ALS5.1, ALS5.2 and ALS10.1 (Oblessuc et al, 2012(Oblessuc et al, , 2013(Oblessuc et al, , 2015. Additionally, three major R genes identified in Andean G5686 (Phg G5686A , Phg G5686B and Phg G5686C ) (Mahuku et al, 2009) were later treated as quantitative loci by Keller et al (2015) and mapped to the same loci as ALS4.1, ALS4.2 and ALS9.1 (Oblessuc et al, 2012;Keller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…All the predicted genes in a 5.5-Mb genomic region (Chr10:3,500,000 … 9,000,000) between the ALS10.1 core border markers IAC61 and BM157 (Oblessuc et al, 2013) were identified using the common bean genome database Phytozome v1.0 (http://www.phytozome.net/). Although a QTL for ALS and anthracnose was mapped to the same region of the ALS10.1 using the DOR364 × G19833 (López et al, 2003), there is no information in the literature regarding the functionality of the ALS10.1 QTL in the G19833 bean reference genotype.…”
Section: Methodsmentioning
confidence: 99%
“…Among the QTL controlling resistance to ALS, ALS10.1 is a major QTL that was mapped to linkage group Pv10 using the IAC-UNA × CAL 143 (UC) recombinant inbreed line (RIL) population (Oblessuc et al, 2012). The ALS10.1 genome core was defined by integrating information on common bean genomic and genetic data using the six molecular markers that span the ALS10.1 region of 5.3 Mb (Oblessuc et al, 2013). …”
Section: Introductionmentioning
confidence: 99%